Association between albumin-bilirubin score and sarcopenia in middle-aged Americans: a cross-sectional study - Zhou, Yifan; Yu, Jinghao; Wu, Anping; Tan, Haitao; Xiao, Jun (Frontiers in Nutrition, 2025)
BackgroundThe albumin-bilirubin (ALBI) score is a novel index for assessing liver function, integrating albumin and bilirubin levels to provide a comprehensive evaluation of a patient’s overall health. Despite its utility, there is a paucity of research exploring the relationship between ALBI scores and sarcopenia in the existing literature, and studies on sarcopenia prevalence in middle-aged adults are also scarce. This study aims to investigate the association between ALBI scores and the prevalence of sarcopenia among middle-aged adults in the United States.MethodsUtilizing data from the National Health and Nutrition Examination Survey (NHANES) collected from 2011 to 2018, participants were classified into prevalent and non-prevalent groups based on sarcopenia status. We constructed one univariate model and two multivariate models, employing restricted cubic spline analysis and weighted logistic regression to examine the relationship between ALBI scores and sarcopenia prevalence. Additionally, subgroup analyses assessed the association between ALBI scores and sarcopenia across various demographic groups. A random forest model was also developed to evaluate the importance of different variables related to sarcopenia, based on Gini impurity.ResultsThe study included a total of 10,354 participants. Analysis of demographic characteristics stratified by sarcopenia prevalence. In the fully adjusted model, a positive association was found between ALBI scores and sarcopenia prevalence [OR (95% CI): 4.28 (2.29, 8.01), p < 0.001]. Furthermore, subgroup analyses indicated no significant interactions across factors such as gender, race, education, marital status, diabetes mellitus, hypertension, smoking, and alcohol consumption. The random forest model revealed an important association between ALBI scores and sarcopenia.ConclusionThis study establishes a significant association between ALBI scores and sarcopenia prevalence in middle-aged adults in the United States. Our findings indicate that higher ALBI scores are correlated with an increased prevalence of sarcopenia, emphasizing the importance of incorporating ALBI scores into assessments of muscle health. These results suggest that ALBI scores could play a crucial role in informing preventive strategies and interventions to combat sarcopenia in this vulnerable population.